A Novel Immunotherapy for Alzheimer's Disease: Antibodies against the β-Secretase Cleavage Site of APP - Arbel, Michal; Solomon, Beka (Current Alzheimer Research, 2007)
One of the main neuropathological lesions observed at brain autopsy of Alzheimer's disease (AD) patients are the extracellular senile plaques mainly composed of amyloid-β (Aβ) peptides. Aβ is generated by proteolytic processing of amyloid precursor protein (APP) via β and γ-secretases. The β-secretase APP cleaving enzyme 1 (BACE1) has become a target of intense research aimed at blocking the enzyme activity. Recent studies showed that BACE1 is involved in processing other non-APP substrates, and that other proteases are involved in APP processing. We have recently established a novel approach to inhibit Aβ production via antibodies against the β-secretase cleavage site of APP. These antibodies bind wild type and Swedish mutated APP expressed in transgenic mice brain tissues. The isolated antibodies do not bind any form of Aβ peptides. Antibody up-take experiments, using Chinese hamster ovary cells expressing wild-type APP, suggest that antibody internalization and trafficking are mediated via the endocytic pathway. Administration of antibodies to the cells growing media resulted in a considerable decrease in intracellular Aβ levels, as well as in the levels of the corresponding C-terminal fragment (C99). The relevance of intra-neuronal accumulation of mainly Aβ42 as an early event in AD pathogenesis suggests that this approach may be applicable as a novel therapeutic strategy in AD treatment.
Keywords: BACE1